Oral health literacy, knowledge and perceptions in a socially and culturally diverse population: a mixed methods study - Shalinie King; Ayesha Thaliph; Liliana Laranjo; Ben J. Smith; Joerg Eberhard (BMC, 2023)
Abstract Background Poor oral health literacy has been proposed as a causal factor in disparities in oral health outcomes. This study aims to investigate oral health literacy (OHL) in a socially and culturally diverse population of Australian adults visiting a public dental clinic in Western Sydney. Methods A mixed methods study where oral health literacy was assessed using the Health Literacy in Dentistry scale (HeLD-14) questionnaire and semi-structured interviews explored oral health related knowledge, perceptions and attitudes. Interviews were analysed using a thematic approach. Results A sample of 48 participants attending a public dental clinic in Western Sydney was recruited, with a mean age of 59.9 (SD16.2) years, 48% female, 50% born in Australia, 45% with high school or lower education, and 56% with low-medium OHL. A subgroup of 21 participants with a mean age of 68.1 (SD14.6) years, 40% female, 64% born in Australia, 56% with a high school or lower education, and 45% with low-medium OHL completed the interview. Three themes identified from the interviews included 1) attitudes and perceptions about oral health that highlighted a lack of agency and low prioritisation of oral health, 2) limited knowledge and education about the causes and consequences of poor oral health, including limited access to oral health education and finally 3) barriers and enablers to maintaining good oral health, with financial barriers being the main contributor to low OHL. Conclusions Strategies aimed at redressing disparities in oral health status should include improving access to oral health information. The focus should be on the impact poor oral health has on general health with clear messages about prevention and treatment options in order to empower individuals to better manage their oral health.